(untitled) (UCC Student Medical Journal, 2024)
Adequate sleep is an important aspect of a healthy lifestyle that increasingly seems to evade many. Factors like elevated stress and poor sleep hygiene are some of the primary culprits behind this, and the consequences they can have on patients’ health are hard to overstate. Insufficient sleep has been documented to have adverse long-term effects on patients’ cardiovascular health, immune systems, and mental well-being, among many other facets of health. Given this, patients with insomnia are at significantly elevated risk of developing these negative health outcomes over time. Insomnia is defined as difficulty with sleep onset or maintenance with associated daytime deficiencies, such as poor concentration. In Ireland, it has been estimated that up to 15% of the population struggle with this potentially debilitating disorder, surpassing some other European populations. Further complicating things, the management of this disorder can be quite difficult and inconsistent. The pharmacological options we currently have at our disposal tend to either have limited efficacy, like melatonin receptor agonists, or carry the risk of dependence, such as benzodiazepines. As for non-pharmacological therapies, our options are extremely lacking, with cognitive behavioural therapy being the only such treatment currently recommended by the Centers for Disease Control and Prevention (CDC).